PERBEDAAN EFEKTIVITAS CORE STABILITY EXERCISE DAN EDUKASI TERHADAP AKTIVITAS FUNGSIONAL PADA PERAWAT DENGAN LBP MYOGENIC DI RS MITRA KELUARGA CIBUBUR - Mohammad Ali; Fahmi Nurqolbi; Achwan Achwan (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
Background: LBP is pain in the lower back due to stress/ strain of the back muscles, tendons, andligaments which are usually felt after doing excessive activities, such as sitting/standing for a longtime, and lifting weights in the wrong position. Nurses are health workers who have a high risk ofdeveloping LBP based on preliminary research which found that 80% of the 20 nurses in the roomwere caused by work activities. Research method Quasi-experimental pre-test and posttest control group design, with a total sample of 19 respondents in each group with a total of 38respondents. The normality test using the SaphiroWilk Test was followed by a Parametric Paired Tteston data that were normally distributed in each group. The results an increase in functionalactivity with a mean difference of 13.68% in the treatment group and an average of 4.74% in thecontrol group. Conclusions there are differences significant effectiveness in the treatment groupwith the results of the Mann-Whitney Test of 0.000 (p<0.05) on increasing functional activity innurses with Myogenic LBP in the treatment room of Mitra Keluarga Cibubur Hospital.